2023
DOI: 10.1111/cbdd.14330
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits malignant behavior of colorectal cancer cells by regulating M2 polarization of tumor‐associated macrophages and metastasis associated in colon cancer 1 (MACC1) expression

Shuke Ge,
Xu Sun,
Limin Sang
et al.

Abstract: The present study was to investigate the underlying mechanism of the antitumor effect of curcumin in colorectal cancer cells, focusing on the M2 polarization of tumor‐associated macrophages (TAMs). The effect of curcumin on the malignant behavior of colorectal cancer cells was investigated by WST assay for cell growth, and Transwell assay for cell migration/invasion. THP‐1 cells were differentiated into macrophages and coculture with colorectal cancer cells to study the influence of curcumin on M2 polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Emerging evidence from both in vitro and in vivo studies suggests that curcumin exerts potent modulatory effects on macrophage polarization in inflammatory diseases, from cancer and autoimmune disorders to renal inflammation, stroke, and atherosclerosis [13]. While curcumin exhibits promising therapeutic potential, its poor solubility and bioavailability limit its clinical applications [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence from both in vitro and in vivo studies suggests that curcumin exerts potent modulatory effects on macrophage polarization in inflammatory diseases, from cancer and autoimmune disorders to renal inflammation, stroke, and atherosclerosis [13]. While curcumin exhibits promising therapeutic potential, its poor solubility and bioavailability limit its clinical applications [48].…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between macrophages and tumors. Recently, Ge SK et al investigated the underlying mechanism of the antitumor effect of curcumin in colorectal cancer cells, focusing on the M2 polarization of tumor-associated macrophages (TAMs) [13]. They concluded that MACC1 and inhibition of M2 polarization of TAMs may mediate the antiproliferative and anti-migratory effects of curcumin in colorectal cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…TNBC cells (SUM159 or 4T1) were starved at 70% confluency for 24 h; then, the cell supernatants were collected and filtered through a 0.45 µm filter to remove cell debris and then stored at −20 • C for further use [55,57,58].…”
Section: Preparation Of Tumor-conditioned Medium (Tcm)mentioning
confidence: 99%
“…8 Research reports that CUR plays a beneficial role in preventing, treating, and controlling cancer symptoms, such as breast cancer, colorectal cancer, prostate cancer, and melanoma. [9][10][11][12] Although CUR may enhance chemotherapy and chemotherapy prevention effects on cancer cells, it is safe and has almost no side effects even at high dose. 13 The evidence from the literature has indicated that CUR is an effective compound with antineoplastic effects.…”
Section: Introductionmentioning
confidence: 99%